PENGARUH MORAL REASONING, SKEPTISME, DAN INDEPENDENSI TERHADAP KUALITAS AUDIT - Mangunsong Benito Dochrist Billyarta (2023)
This study conducted to examine the effect of the Quality of the Audit on Moral Reasoning, Skepticism, and Independence. This research is a quantitative research with primary data types using a questionnaire and a Likert scale as a measuring tool. The population in this study were all auditors who work at KAP South Jakarta. Determination of the sample in this study using a purposive sampling technique. A total of 148 questionnaires were distributed and all questionnaires were returned and could be processed. The data analysis method used is Structural Equation Modeling (SEM) analysis. The results of the study show that skepticism and independence have an effect on the quality of the audit. While the Moral Reasoning variable has no effect on the Quality of the Audit.